(untitled) - Watson, David H. (New York, 2004)
Now more than ever, producing safe foods is of paramount importance for public safety. As the food industry strives to balance methods for efficient food production with overall safety, new research must be analyzed to quickly incorporate safe standards. A state-of-the-art reference, however, has not been available until now.
Keywords: Pesticides,Food conservation